An experimental study of laminar ammonia/methane/air premixed flames using expanding spherical flames. (15th April 2021) - Shu, Tao; Xue, Yuan; Zhou, Zijun; Ren, Zhuyin
Highlights: The laminar flame properties of ammonia/methane fuel blends are reported. The laminar flame speeds have strong linearity with methane content in blends. The flammability limits vary almost linearly with methane contents in blends. Pressure has a pronounced impact on upper limits but not on lower limits. Linearity between flame speeds and H + OH radical concentrations is observed. Abstract: The fundamental flame properties of ammonia/methane/air mixtures were experimentally investigated using expending spherical flames in a constant pressure chamber. The laminar flame speeds, Markstein lengths and flammability limits were reported for ammonia/methane fuel blends with the equivalence ratios varying from 0.6 to 1.4, at room temperature (298 K) and different pressures (1.0, 5.0 atm). The measured flame properties are compared to those from one dimensional freely propagating flames to assess the accuracy of three existing detailed chemical mechanisms for ammonia/methane/air mixtures. Results show that for ammonia/methane/air mixtures, the laminar flame speeds have a linear correlation with the methane volume fraction. Over the whole ranges of equivalence ratio and methane volume fraction considered, the mechanism of Okafor et al. can accurately predict the laminar flame speeds. With increasing methane content in the fuel mixture, both upper and lower flammability equivalence ratio limits are broadened, and the flammability concentration limits decrease uniformly. In addition, pressure has a pronounced impact on upper limits, while its impact on lower limits is negligible. Sensitivity analysis shows that radicals H, OH (H, OH and CH3 ) play crucial roles in flame propagation of fuel lean (rich) flames. For fuel lean flame propagation, linear correlations between laminar flame speeds and radical concentrations of H + OH are observed for a wide range of pressures and methane volume fractions.